Classroom disciplinary climate of schools and gender – evidence from the Nordic countries. Issue 4 (2nd October 2018) - Sortkær, Bent; Reimer, David
ABSTRACT: Classroom disciplinary climate has emerged as a crucial factor with regard to student achievement. However, most previous studies have not explored potential gender differences in both students' perceptions of the classroom disciplinary climate and the association between classroom disciplinary climate and student learning. Using data from the Organisation for Economic Co-operation and Development (OECD) Programme for International Student Assessment (PISA) 2012 for the Nordic countries, we found a significant association between the perceived classroom disciplinary climate of schools and students' mathematics performance across countries. On the basis of an analysis of a pooled sample consisting of all 5 Nordic countries, we found that the correlation between classroom disciplinary climate of schools and maths achievement is significantly stronger for boys than for girls. Further analyses showed that this finding may partly be attributable to gender differences in the perception of the disciplinary climate of schools, whereby boys seemed to perceive the classroom disciplinary climate of schools more positively than girls.